Stuart Little 2 - Infogrames (Firm) (New York Infogrames, 2002)
Join Stuart Little for big adventures-- fly high over Central Park, skateboard over rooftops or navigate around street-level obstacles in Stuart's car and more
Title from disc surface
System requirements: Windows 98/ME/XP; Pentium II 233 MHz+; 32 MB RAM (64 MB for XP); 100 MB HD; 4X CD-ROM drive; 2 MB video card; sound card; DirectX 8.1 (included) or higher
1
Keywords: Mice -- Computer games; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs